(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
The aim of this research was to find periodic explicit soliton wave solutions for Benjamin-Bona-Mahony equation with time-dependent coefficients using the sin-cos method taking nonlinear wave transform with time dependent velocity. We found bright soliton wave solutions using a solitary wave ansatz method. We have also presented condition of existence of this solutions. This kind of solutions is very useful for understanding most nonlinear physical phenomena, especially those that are considered an application of wave theory.